Pembelajaran Mobile Learning Berbasis Android Untuk Meningkatkan Prestasi Belajar Siswa Pada Materi Bangun Ruang Sisi Lengkung - Ruslimin A (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research focuses on the use of learning media to improve student learning achievement in curved geometric shapes. The research subjects taken were 11 students at one of the Madrasah Tsanawiyah (Mts) schools. There are two learning media designed in this research, namely ICT and non-ICT media. ICT media is in the form of Android-based mobile learning, while non-ICT media contains information about determining the volume of a ball using a cone approach. The results of this research show that Android-based mobile learning can improve student learning achievement in curved geometric shapes.